Precooling's effect on American football skills - Bradley, L. J.; Miller, K. C.; Wiese, B. W.; Novak, J. R. (The Journal of Strength and Conditioning Research, 2019)
Precooling (i.e., cooling before exercise) may reduce the risk of exertional heatstroke (EHS) in American football athletes. However, implementation of precooling by coaches or medical staff would likely be poor if it impaired performance. We investigated whether precooling impacted American football skill performance in this randomized, crossover, counterbalanced study. Twelve men (24 ± 2 years, mass = 85.5 ± 6.3 kg, height = 181.8 ± 8.1 cm) completed a familiarization day to practice each skill and then 2 testing days. On testing days (wet-bulb globe temperature = 19.3 ± 4.1° C), subjects were either precooled for 15 minutes using cold-water immersion (10.1 ± 0.3° C) or not (control). Then, they donned an American football uniform and completed several bouts of 8 different football skills. Rectal temperature (Trec) was measured before, during, and after skill testing. Precooling did not affect vertical jump, broad jump, agility, dynamic or stationary catching, or maximum throwing distance (p >= 0.13). Precooling impaired 40-yard dash time (precooling = 5.72 ± 0.53 seconds, control = 5.31 ± 0.34 seconds; p = 0.03, effect size = 1.2) and throwing accuracy (precooling = 4 ± 1 points, control = 7 ± 2 points; p = 0.001, effect size = 1.4). On average, Trec was 0.58 ± 0.35° C lower during skills testing after precooling and statistically differed from control from minute 10 to the end of testing (~35 minutes; p < 0.05, effect size >= 1.2). Precooling may be a useful EHS prevention strategy in American football players because it lowered Trec without impacting most skills. By lowering Trec, precooling would prolong the time it would take for an athlete's Trec to become dangerous (i.e., >40.5° C). If precooling is implemented, coaches should alter practice so that throwing accuracy and speed drills occur after an athlete's Trec returns to normal (i.e., >35 minutes).